FAKTOR TEKNOLOGI TERHADAP ADOPSI BIG DATA PADA ERA TRANSFORMASI DIGITAL - Ratnasari, Mega Ayu; Hasnawati (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2023)
This study aims to analyze the influence of technological factors on the adoption of big data analytics in the digital transformation era. The population in this study are companies in Indonesia, especially those in Jabodetabek that have adopted big data in their operational systems. The sample in this study was 205 respondents using a purposive sample method. The type of data in this study is primary data in the form of a questionnaire survey. Data were analyzed using multiple regression techniques using SPSS ver 25. The study results show that relative advantage, compatibility, and complexity positively affect companies' interest in adopting big data. But security negatively affects companies' interest in adopting big data.